Diferencias sexuales en la violencia desde la perspectiva de la psicología evolutiva: análisis de datos bioarqueológicos de sociedades andinas precoloniales - Pinto dos Santos, Felipe (2021)
Motivated by an evolutionary look to understand the origins and circumstances of the practice of physical violence, this study analyzes quantitative data on head injuries in adult individuals, male and female, from pre-colonial Andean populations and discusses its results from the perspective of Evolutionary Psychology, particularly, to explain violent behaviour among males. The results point to a higher prevalence of males in the practice of violence and reveal aspects of the phenomenon that can be studied in the future, such as the differential circumstances of the occurrence of trauma related to gender in past populations.